ANALISIS GELOMBANG AKUSTIK TERHADAP PENGARUH TEKANAN CASING DAN GAS HETEROGEN UNTUK MENENTUKAN KEDALAMAN LIQUID LEVEL SUMUR MINYAK MENGGUNAKAN DATA SONOLOG - Suhardi '; Usman Malik; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been done in analyzing an acoustic wave and its effect to casing pressure and gas flow at annulus in order to determine liquid level depth of oil well. The research used an experiment method using sonolog type remote fire gas gun with its sound wave frequency between 30 Hz – 60 Hz. Data were taken from three oil wells that are managed by the Unit of business Pertamina EP Lirik. Each well was measured five times at different time. The data obtained were analyzed by Total Well Management (TWM) software. They were acoustic velocity, casing pressure, and gas flow. The value of acoustic velocity shown by TWM sometimes didn’t match to the real condition including the data of determined liquid level depth. New value of acoustic velocity had been gotten using multiple regression linear equation. Time travel of wave was measured using Down Hole Marker at TWM. Result of calculation of acoustic velocity based on measured data for well LS-031 at November 24th 2011 was 397,7138 m/s, for well LS-105 measured at March 13th 2010 was 359,6792 m/s, for well LS-105 measured at November 25th was 356,17 m/s. Results of calculation of liquid level depth for well LS-031 was 249,9634 m, for well LS-105 was 261,23 m, and for well LS-097 was 246,96 m.